Characteristic of Husk Charcoal, Bokashi Compost, and Wood Charcoal as Biofilter Filler on Application of Ammonia 5 Percent - Juliana Siregar, Mia; ., . (International Journal of Engineering and Technology, 2018)
Bio-filter has been widely used as one of methods to remove odorous gas, because of inexpensive, easy, and can remove the odour perfectly. This research has been conducted in order to determine the best physical of characteristic of bokashi compost, husk charcoal, and wood charcoal toward the adsorption of ammonia and compositions of such materials. 5% of Ammonia solution has been used to the physical characteristic of packing material. Some methods which use was water content and density, porosity, pressure drops, Water Holding Capacity (WHC), Pollutant Holding Capacity (PHC). Data were analyzed by ANOVA statistic test with error value 5% and continued with Duncan Test. From the physical experiment, by performance ranking shows husk charcoal is better than wood charcoal, and compost. Husk carbon shows the highest porosity, availability in hold water and air, PHC, and pressure drops. Husk carbon can adsorb 1.18x10-3 g-N/g bk of ammonia. Treatment of material composition with a ratio of (K212) shows that it is the best composition in ammonia absorption. This is evident from the water content of K212, lower pressure drops, PHC of 1.8x10-4 g-N / g bk. The conclusions are husk charcoal can be used as an alternative material absorbent of ammonia pollutant which is good enough seen from its physical character and the addition of wood charcoal as a filler composition can improve the physical character of the material as a filler on the mixture of compost material bokashi and charcoal husk. Â Â